Televisi Sebagai Media Dakwah Islam Dalam Kehidupan Masyarakat Indonesia - Nurliana (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2020)
Da'wah which initially only uses traditional media, then develops by using the touches of modern technology including television. Television is one of the modern media that can be used to preach today. Television has one goal, which is to attract people's attention to the content of the message conveyed. As a medium of communication, television can play its role as an interesting channel to convey messages of kindness to the public. Including religious messages that are commonly called da'wah. The advantages of propaganda through television media do not only depend on the advantages possessed by this media. Likewise for a Preacher who wants to take advantage of television media, he is required to fully understand how to use this media, including determining the methods and techniques of preaching. Because without the proper methods and techniques of da'wah in using television media, it will only waste energy and costs, and will also increase the distance of Da'wah activities with the community. This research uses content analysis.